Discovery of a new subgroup of sulfur dioxygenases and characterization of sulfur dioxygenases in the sulfur metabolic network of Acidithiobacillus caldus - Wu, Wei (PLoS One, 2017)
Acidithiobacillus caldus is a chemolithoautotrophic sulfur-oxidizing bacterium that is widely used for bioleaching processes. Acidithiobacillus spp. are suggested to contain sulfur dioxygenases (SDOs) that facilitate sulfur oxidation. In this study, two putative sdo genes (A5904_0421 and A5904_1112) were detected in the genome of A. caldus MTH-04 by BLASTP searching with the previously identified SDO (A5904_0790). We cloned and expressed these genes, and detected the SDO activity of recombinant protein A5904_0421 by a GSH-dependent in vitro assay. Phylogenetic analysis indicated that A5904_0421and its homologous SDOs, mainly found in autotrophic bacteria, were distantly related to known SDOs and were categorized as a new subgroup of SDOs. The potential functions of genes A5904_0421 (termed sdo1) and A5904_0790 (termed sdo2) were investigated by generating three knockout mutants (Δsdo1, Δsdo2 and Δsdo1&2), two sdo overexpression strains (OE-sdo1 and OE-sdo2) and two sdo complemented strains (Δsdo1/sdo1’ and Δsdo2/sdo2’) of A. caldus MTH-04. Deletion or overexpression of the sdo genes did not obviously affect growth of the bacteria on S(0), indicating that the SDOs did not play an essential role in the oxidation of extracellular elemental sulfur in A. caldus. The deletion of sdo1 resulted in complete inhibition of growth on tetrathionate, slight inhibition of growth on thiosulfate and increased GSH-dependent sulfur oxidation activity on S(0). Transcriptional analysis revealed a strong correlation between sdo1 and the tetrathionate intermediate pathway. The deletion of sdo2 promoted bacterial growth on tetrathionate and thiosulfate, and overexpression of sdo2 altered gene expression patterns of sulfide:quinone oxidoreductase and rhodanese. Taken together, the results suggest that sdo1 is essential for the survival of A. caldus when tetrathionate is used as the sole energy resource, and sdo2 may also play a role in sulfur metabolism.